Solid state bioreactor for food waste composting: a process optimization - Alam, Md. Zahangir; Samiha, Siti; Deb, Nibedita (College of Engineering, Universiti Tenaga Nasional, 2020)
Compost production, an aerobic biodegradation process is one of the alternatives ways to manage and reuse the waste in order to produce compost product with high commercial value for agricultural applications. The longer reaction time of the composting process is one of the barriers for high rate of compost production. Therefore, this study is carried out to evaluate the shorter composting period by optimization technique in a solid state bioreactor/composter at thermophilic condition. Among the parameters studied, the selected parameters to be considered were temperature and rotation (mixing) time of the horizontal stirred tank solid state bioreactor (HST-SSB). A statistical design was applied to determine the optimum parameters in the reactor. A set of temperatures at 60-800C which are under thermophilic conditions was chosen to determine the optimum temperature to produce high nutrient content of compost product and 12,16 and 20 hours as the total rotation time per day (24 hours). The food waste was fed at 20-25 kg/day with 20% of saw dust as bulking agents per batch with the microbial inoculum that contain effective microorganisms (EM). The EM was used for faster biodegradation with highly active hydrolytic enzymes as well as it increases the microbial diversity of soil ecosystem. The optimum temperature and rotation time were determined by two-level fractional factorial design (FFD). Decomposition of the food waste was completed in 6 days and harvesting at day 7. The results showed that the optimum temperature and rotation time of the HST-SSB were 600 C and 12 hrs/day with the pH value of 6.2 for the compost product with C/N ratio of 13 and 85% of the germination index.